The Effectivesness of Storytelling to Teach Speaking Skill: An Experimental Study at Ninth Grade Students of SMPN 11 Mataram Academic Year 2022/2023 - Rabianti Rabianti; Yuni Budi Lestari; Arafiq Arafiq; Lalu Muhaimi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
The study investigated the effectiveness of storytelling as a teaching technique for speaking skills among ninth-grade students at SMPN 11 Mataram. The research method employed a pre-experimental design, specifically a group pretest and post-test design. The target population consisted of ninth-grade students at SMPN 11 Mataram, with a sample size of 28 students from class IX C. Data were collected through three stages: pretest, treatment, and post-test. The pretest served as a baseline measurement, with a mean score of 70.57. The treatment phase involved implementing the storytelling technique, and finally, the post-test was conducted to assess the students' speaking skills after the treatment. The post-test was a higher mean score of 82.28, indicating a 16% improvement compared to the pretest. A paired sample t-test was conducted in this study. The t-test value was compared to the t-Table value to assess the difference between the pretest and post-test means. In this case, the t-test value was higher than the t-Table value, leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho). This implies that the storytelling technique was effective in teaching speaking skill to ninth-grade students at SMPN 11 Mataram in the academic year 2022/2023. The results showed a significant improvement in speaking skill after the implementation of the storytelling technique.